Effectiveness Microcapsules From Auxin Producing-Endophite Bacteria As Biofertilizer in Tea (Camellia sinensis L) - Zit, Sigit Indra; Warsito, Kabul; Refnizuida, Refnizuida (Universitas Labuhanbatu, 2023)
Tea (Camellia sinensis L), is a popular agricultural product enjoyed by people around the world. Bio-fertilizers that use bacteria found in soil called endophytes, have proven effective for increasing growth and plant productivity. Endophite bacteria can also produce growth hormones such as auxins, ethylene, and cytokinins. This research aims to determine the effectiveness of auxin-producing endophytic bacterial microcapsules on tea growth. The research design used was a completely randomized design (CRD), 16 treatments with 2 replications. The first factor was immersion of endophite bacterial suspension consisting of S0 = 0 hours; S1 = 24 hours; S2 = 36 hours and S3 = 48 hours and the second factor was the addition of microcapsules consisting of I0 = 0 gr; I1 = 5 gr; I2 = 10 gr; I3 = 15 gr. Isolation from tea roots and stems obtained 6 isolates of endophite bacteria. Auxin test showed that the six isolates were able to produce auxin. Observation of plant height showed that the best treatment was in treatment I3 (17.04 cm). Observation of leaves amount was in treatment I3 (6.88 strands). For the leaf area parameter, the highest number was in the S1 treatment (22.8 cm2). For stem diameter parameter, highest data was in treatment I2 (1.69 mm). The test results showed that the application of suspension and endophite bacteria microcapsules significantly increased the growth of tea.